WHICH ASPECTS OF THE ENGLISH LANGUAGE DO DISTANCE LEARNERS FIND DIFFICULT? - Teoh, George Boon Sai; Lin, Agnes Liau Wei; Belaja, Kathy (Anadolu University, 2016)
This study reports the findings of a research carried out on distance learners at the School of Distance Education (SDE), University Sains Malaysia (USM). The study was explorative in nature with the purpose identifying the aspects of the English language which distance learners found difficult to learn. A quantitative survey questionnaire design was adopted. The sample consisted of 512 students out of 1028 students who enrolled in the JUE300 English II course responded. The data were analyzed using SPSS IBM version 19.0. The distance learners reported facing difficulties in the aspects of speaking, vocabulary, grammar, writing, spelling, pronunciation, reading and listening in descending order. In the case of the SDE distance learners, their level of proficiency prior to this course, their commitment and hours spent on studying the English language may have affected their perceptions and achievement in the course.